Acesso venoso central em crianças guiado por ultrassom - Zanolla, Gabriela Ruschel (2014)
Objective: The objective is to determine if ultrasound guidance for internal jugular vein catheterization can be safely performed, improving success rates and diminishing the procedure lenght and complication rates. Methods: Prospective randomized trial submiting 51 patients to central venous access. 1:1, on gender and age. The patients selected were between 0yrs 18yrs Tha data analysis was made utilizing the Mann-Whitney Test and Pearson s qui-squared. Results: 51 patients were submited to central venous access to internal jugular vein. 23 were US guided, and 28 procedures utilized landmark method. There was no difference betwwen groups on age and weight wise, The number of punctions to access the vein were smaller in the US group md(P25-P75) 3(2-5) X 1(1-2)p<0,001, and faster too. There was a decrease n complication rates using the US from 39% to 4,3% (p<0,009), Conclusions: The present data suggest that ultrasound guided catheterization of the internal jugular vein is more successful than the landmark method: was more rapidly done, had greater success rates and less complication rates and number of punctions.